Peningkatan Kemampuan Menulis Teks Prosedur Kompleks Melalui Metode Quantum Writing Siswa Kelas XI SMA Negeri 3 Rejang Lebong - Ifnaldi Ifnaldi ifnaldi (Universitas Nahdlatul Wathan Mataram, 2023)
Indonesian language learning at SMA Negeri 3 Rejang Lebong conducted by teachers has not shown quality, so students feel bored, less active in learning and student learning outcomes are still low. This study aims to determine the performance of the model and determine the improvement of learning outcomes through the application of the Quantum Writing method. This study used the Classroom Action Research (CAR) method which was carried out in two cycles. Each cycle consists of one meeting, and each cycle consists of four stages, namely planning, implementation, observation, and reflection. Research data obtained by using student activity observation sheets and tests. The results obtained are (1) the ability to write complex procedural texts in class XI students of SMA Negeri 3 Rejang Lebong before using the Quantum Writing method, the student's score is still below the KKM that does not meet the desired criteria. (2) the ability to write complex procedure texts using the Quantum Writing Method in class XI students of SMA Negeri 3 Rejang Lebong has increased. This is indicated by an increase in the average value before and after being given treatment. The mean score on the initial test was 40% increasing to 80% on the final test.